Pengelolaan Arsip Inaktif di Sekretariat DPRD Provinsi Sumatera Barat - Virsefni, Widia; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2012)
Abstract The purpose of this research is to describe the activity in the Representative of Sumatera Barat about : (1) the source of inactive archives; (2) the archives which include into inactive one; (3) the record system of inactive archives; and (4) if the inactive archives has been reduce or not. The data was collected through observation and interview. Data analisys was processed by descriptive technique. Based on data analisys, it can be conclude that. First, the source of inactive archives that been put into storage comes from the meeting of the Representative. Second, there are only two kinds of inactive archives, specific archives and special archives. Third, the record system that used by the Representative of Sumatera Barat is the chronological system. Fourth, there is no reduction activity for the archives. Keywords: Records management; inactive archive